1990
DOI: 10.1002/j.1460-2075.1990.tb08172.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha subunit variants of the human glycine receptor: primary structures, functional expression and chromosomal localization of the corresponding genes.

Abstract: Two cDNAs encoding variants (alpha 1 and alpha 2) of the strychnine binding subunit of the inhibitory glycine receptor (GlyR) were isolated from a human fetal brain cDNA library. The predicted amino acid sequences exhibit approximately 99% and approximately 76% identity to the previously characterized rat 48 kd polypeptide. Heterologous expression of the human alpha 1 and alpha 2 subunits in Xenopus oocytes resulted in the formation of glycine‐gated strychnine‐sensitive chloride channels, indicating that both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
162
0
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(168 citation statements)
references
References 35 publications
5
162
0
1
Order By: Relevance
“…Previous studies have demonstrated that the human GlyR CL? subunit forms strychnine-sensitive chloride channels upon heterologous expression in Xenopus oocytes [16]. Accordingly, large glycine-gated currents were revealed here in cotransfected cells by voltage-clamp recording (Fig.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…Previous studies have demonstrated that the human GlyR CL? subunit forms strychnine-sensitive chloride channels upon heterologous expression in Xenopus oocytes [16]. Accordingly, large glycine-gated currents were revealed here in cotransfected cells by voltage-clamp recording (Fig.…”
Section: Resultsmentioning
confidence: 60%
“…The human CilyR a: [16] and the rat GlyR a, [18] and/3 [5] subunit cDNAs as well as the rat gephyrin pl cDNA [S]. each subcloned into the eukarydtic expression vector pCIS, were used to transfcct the human ombyronic kidney cell line 293 (ATCC CRL1573) by calcium phosphate precipitation as described [20].…”
Section: Tmrsjraiott Of 293 Kidney Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the 48 kDa polypeptide is able to form homomerit channels when expressed in oocytes or mammalian cells [IS,191, and has also been shown to be phosphorylated in vitro by protein kinase C [20]. Furthermore, recent reports indicate the existence of several different mRNAs encoding subtypes of the 48 kDa GlyR subunit in both the neonatal and the adult rat spinal cord [l&21,22] and two different 48 kDa subunit genes located in different chromosomes have been recently detected in humans [23]. This expected molecular heterogeneity would be similar to the receptor subtype diversity found for other ion channel-linked neuroreceptors homologous to the GlyR, such as the GABAA and the neuronal nicotinic acetylcholine receptors (see [24] for a review), Further experiments are needed to ascertain the molecular basis of the existence of functionally different forms of the glycine receptor and to fully characterize the electrophysiology of the ionic channels involved.…”
Section: Resultsmentioning
confidence: 99%